Cardiovascular diseases and energy deficiency: pathogenetic ways of correction - M.S. Cherska; H.M. Kukharchuk (Медицина неотложных состояний, 2023)
Cardiovascular disease remains one of the most common and influential causes of death worldwide, as the heart plays a key role in the human body. Energetic cardioprotective therapy of the myocardium is an important protective factor, regulating the synthesis and use of energy by myocardial cells, while having a little effect on heart rate, blood pressure, and blood supply. Phosphocreatine plays an important role in the intracellular energy buffering and transport system, ensuring energy transfer from the site of production to the site of use to meet the high and variable demands of the heart. Research shows that phosphocreatine can have a positive effect on patients with coronary heart disease, heart failure, and those who have undergone cardiac surgery. The accumulated information confirms the prospects of using phosphocreatine in clinical practice to improve treatment outcomes in patients with heart diseases.